An economic evaluation of restorative justice post-sentence in England and Wales - Frank Grimsey Jones; Lucy Jaffé; Lucy Harris; Jon Franklin; Lisa Allam; Joanna Shapland (Frontiers in Psychology, 2023)
IntroductionParticipation in restorative justice interventions post-sentence has been shown to reduce reoffending and mitigate harm to victims. Investment in, and access to, restorative justice remains limited in England and Wales. An economic model was developed to synthesize the available evidence in order to develop contemporary and robust estimates of the economic impact of investment in restorative justice interventions.MethodsThis research focused on direct and indirect restorative justice interventions for victims and offenders post-sentence in England and Wales. Included offences were those with an identifiable victim. A model was developed to estimate the social benefit–cost ratio of restorative justice, as well as the direct financial return to the criminal justice system. The modeled benefits of restorative justice included reductions in reoffending and direct wellbeing benefits for victims. It was not possible to incorporate direct wellbeing benefits for offenders due to evidence gaps.ResultsIn the model, 8% of referrals to restorative justice resulted in direct restorative justice interventions and 19% resulted in indirect Restorative justice interventions. The modeled cost of the restorative justice pathway per direct intervention was £3,394. The base case estimate for the social benefit–cost ratio of restorative justice was £14 per £1 invested, with a direct return to the criminal justice system of £4 as a result of substantial reductions in reoffending. Scenario analysis suggested a plausible range of £7 to £20 social benefit per £1 invested. Hypothetically, increasing the proportion of eligible cases referred for a restorative justice intervention from 15 to 40% could be associated with an increase in investment of £5 m, and benefits to the criminal justice system totaling £22 m, implying a net saving of £17 m.ConclusionThe research suggests that Restorative justice has the potential to yield a substantial social return on investment (SROI) and direct return on investment to the criminal justice system. The economic case for investment in restorative justice centers on identifying offenders with a high risk of offending and enabling them to participate in an intervention that has been repeatedly demonstrated to help them to change their behavior.